Differences between peptide profiles of extensive hydrolysates and their influence on functionality for the management of cow's milk allergy: A short review - Goh, Anne; Muhardi, Leilani; Ali, Adli; Liew, Woei Kang; Estrada-Reyes, Elizabeth; Zepeda-Ortega, Benjamin; Kudla, Urszula; van Neerven, R. J. Joost; Ulfman, Laurien H.; Lambers, Tim T.; Warner, John O. (Frontiers in Allergy, 2022)
Extensively hydrolyzed formula(eHF) is recommended for the dietary management of cow’s milk protein allergy(CMPA) in non-exclusively breastfed infants. Studies show that peptide profiles differ between eHFs. This short review aims to highlight the variability in these peptides and their ability to influence allergenicity and possibly the induction of tolerance by different eHFs. The differences between eHFs are contributed by the source of the protein fraction (casein or whey), peptide size-distribution profile and residual β-lactoglobulin resulting from the hydrolyzation process. This results in differences in IgE reactivity against cow’s milk allergen epitopes by subjects with CMPA and differences in Th1, Th2 and pro-inflammatory cytokine responses elicited. The eHFs demonstrated different effects on gut barrier integrity and cytokine responses. Results suggest that one particular eHF-C had the least allergenic potential due to its low residual allergenic peptide content and demonstrated the greatest effect on restoring gut barrier integrity by its effects on mucin 5AC, occludin and ZO-1 in human enterocytes and increased production of the tolerogenic cytokines Il-10 and IFN-γ. This review highlights differences in the residual allergenicity and functionality of different eHFs which can impact the management of CMPA and the ability to induce tolerance to cow’s milk protein.